Deviant Behavior of Adolescents in the Digital Era from the Perspective of Islamic Education - Arik Febroza; Alwi Mulya; Ade Darmawan; Praja Purnama Nusa; Janu Darmansyah; Perdi Gusti Cahyadi (al-Afkar, Journal For Islamic Studies, 2026)
The digital era has reconstructed the social interaction space that offers communication efficiency as well as massive moral challenges, where the penetration of information technology that is not accompanied by spiritual maturity has triggered various digital social pathologies such as cyberbullying, hoaxes, flexing, and addiction to immoral content. This study aims to analyze the phenomenon of deviant behavior in cyberspace through the perspective of Islamic Religious Education (PAI) and formulate a holistic strategy for overcoming it using descriptive qualitative methods with a literature study approach (library research) that synthesizes findings from various recent literature related to education, ethics, and digital sociology. The results of the analysis show that deviant behavior in cyberspace is rooted in an identity crisis, loss of empathy due to digital anonymity (online disinhibition effect), and erosion of adab, so as a fundamental solution, this study offers a "Digital Piety" framework based on the value of muraqabah (transcendental awareness) and the revitalization of the epistemology of "Adab before Knowledge". Further analysis reveals that the deconstruction of morality in the virtual space is triggered by a shift in value authority that is now dominated by social media algorithms, which requires Islamic Education to reposition its methodological approach from a doctrinal approach to a persuasive-dialogical one in order to instill spiritual intelligence as an antidote to identity commodification and digital narcissism. The conclusion of this study emphasizes that overcoming digital moral decadence requires strategic synergy between value-based digital literacy in educational institutions and strengthening spiritual resilience in the family ecosystem, with recommendations for developing an Islamic Religious Education curriculum that is adaptive to the dynamics of digital sociology to produce individuals with moral autonomy and strong moral integrity in the era of disruption.